Response to targeted therapy or chemotherapy following immunotherapy in patients with gastrointestinal cancers - a case series. Issue 1 (27th June 2019) - Alsuwaigh, Rayan; Lee, Joycelyn; Chan, Gloria; Chee, Cheng Ean; Choo, Su Pin
Abstract : Background: In non-small cell lung cancer, response rates to chemotherapy given after immune checkpoint inhibitors has been reported to be higher compared to response rates to chemotherapy given before immune checkpoint inhibitors. However, this phenomenon has not been reported in patients with gastrointestinal cancers nor with the use of multi-targeted kinase inhibitors. Case presentation: We present a series of six patients who received multi-targeted kinase inhibitors or chemotherapy after progression on immune checkpoint inhibitors and showed unexpected response. Five of these patients had metastatic hepatocellular carcinoma and received salvage multi-targeted kinase inhibitors. Two of these five patients had no response to initial multi-targeted kinase inhibitors but had unexpected response to re-challenge with multi-targeted kinase inhibitors after immune checkpoint inhibitors exposure. The sixth patient had metastatic rectal cancer and showed response to salvage chemotherapy following immune checkpoint inhibitors. Conclusion: We postulate that the sequencing of immune checkpoint inhibitors prior to other forms of systemic therapy may potentially lead to an immunomodulatory effect in gastrointestinal cancers with potential improvement in response rates.